Within-host microevolution of Pseudomonas aeruginosa in Italian cystic fibrosis patients. Issue 1 (December 2015) - Marvig, Rasmus; Dolce, Daniela; Sommer, Lea; Petersen, Bent; Ciofu, Oana; Campana, Silvia; Molin, Søren; Taccetti, Giovanni; Johansen, Helle
Abstract Background Chronic infection withPseudomonas aeruginosa is a major cause of morbidity and mortality in cystic fibrosis (CF) patients, and a more complete understanding ofP. aeruginosa within-host genomic evolution, transmission, and population genomics may provide a basis for improving intervention strategies. Here, we report the first genomic analysis ofP. aeruginosa isolates sampled from Italian CF patients. Results By genome sequencing of 26 isolates sampled over 19 years from four patients, we elucidated the within-host evolution of clonal lineages in each individual patient. Many of the identified mutations were located in pathoadaptive genes previously associated with host adaptation, and we correlated mutations with changes in CF-relevant phenotypes such as antibiotic resistance. In addition, the genomic analysis revealed that three patients shared the same clone. Furthermore, we compared the genomes of the Italian CF isolates to a panel of genome sequenced strains ofP. aeruginosa from other countries. Isolates from two of the Italian lineages belonged to clonal complexes ofP. aeruginosa that have previously been identified in Danish CF patients, and our genomic comparison showed that clonal isolates from the same country may be more distantly related than clonal isolates from different countries. Conclusions This is the first whole-genome analysis ofP. aeruginosa isolated from Italian CF patients, and together with both phenotypic and clinical information this dataset facilitates a more detailed understanding ofP. aeruginosa within-host genomic evolution, transmission, and population genomics. We conclude that the evolution of the Italian lineages resembles what has been found in other countries.